Learning Disability (Dysgraphia): A Case Study on a Second Grade Student at Elementary School - Yuniari, Ni Made (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Student who had difficulty in writing, especially if asked to write cursive letters. There were several writing difficulties faced by students such as the student's lack of focus in copying the writing on the board, this made student was slow in completing work. This study aims to analyze the learning writing disorder experienced by the student and ways to overcome the student's writing disorder. The qualitative research study that explores a second-grade student's writing issue. This research attempts to define the student's learning (writing) disorder, the type of learning disorder the student has, and solutions to overcome the student's writing issue. To collect data from second-grade students at elementary school the study used a case study design and descriptive approach. This study employed a qualitative research design using descriptive methodology and a case study approach. This study utilized direct observation, interviews, and documentation. Data analysis techniques in this research consisted of three stages: data collection, data reduction, and drawing conclusions. The study's findings indicate that the student problems with arranging written work on paper, spelling, and uneven spacing. The research closes by advising that the student get special education programs to address his or her writing problem.